Construction of strongly-coupled CeO2/MnO2 heterogeneous catalysts for highly-efficient removal of formaldehyde. (10th March 2023) - Zhang, Shuaishuai; Zhang, Lingling; Liu, Li; Chu, Xiang; Wang, Xiao; Song, Shuyan; Zhang, Hongjie
Abstract : Formaldehyde (HCHO) is highly toxic, but its low-temperature elimination is still a pressing challenge nowadays. Abstract : Formaldehyde (HCHO) is highly toxic, but its low-temperature elimination is still a pressing challenge nowadays. In this work, we demonstrate an interface engineering strategy to boost the catalytic performance of the promising MnO2 catalysts by coupling the CeO2 promoters on the surface. The as-prepared CeO2 –MnO2 mixed-metal oxide (CeMn- x ( x = 0.1, 0.5, and 1)) catalysts with a Ce/Mn ratio of 0.5/10 possess excellent catalytic activity and a relatively low T 100 (the temperature for 100% HCHO conversion) of 95 °C is achieved. More oxygen vacancies, outstanding redox ability, and the strong interaction between CeO2 and MnO2 are responsible for the enhanced catalytic activity of CeMn. This study provides novel insight into the design of MnO x catalysts for the purification of HCHO at low temperatures.